2014
DOI: 10.1002/rcm.7073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decalcification on bulk and compound‐specific nitrogen and carbon isotope analyses of dentin

Abstract: Decalcification is not needed to measure bulk isotope values in dentin from this modern odontocete, probably because the lipid and carbonate concentrations are low and the carbon isotope values of dentin protein and carbonate are similar. This method should not be applied in some cases (e.g., with fossil dentin and modern bone). Decalcification should still be used prior to CSIA since significant matrix issues occur with raw dentin processing and decalcification does not alter the amino acid molar composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…The close correspondence of the CSI‐AA patterns that we observed in most samples of both fossil and modern shell with CSI‐AA patterns in soft tissue, coupled with the low and generally similar ΣV values, clearly indicates that this protocol does not measurably fractionate individual AA isotope ratios. This finding is in contrast to recent work testing CSI‐AA patterns using different modes of demineralization for phosphate‐rich dentin . This work by Brault and coauthors indicated that when phosphates are present, all inorganic ions must be removed in order to produce the expected CSI‐AA patterns, and also to obtain reproducible δ 15 N AA values.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The close correspondence of the CSI‐AA patterns that we observed in most samples of both fossil and modern shell with CSI‐AA patterns in soft tissue, coupled with the low and generally similar ΣV values, clearly indicates that this protocol does not measurably fractionate individual AA isotope ratios. This finding is in contrast to recent work testing CSI‐AA patterns using different modes of demineralization for phosphate‐rich dentin . This work by Brault and coauthors indicated that when phosphates are present, all inorganic ions must be removed in order to produce the expected CSI‐AA patterns, and also to obtain reproducible δ 15 N AA values.…”
Section: Discussionmentioning
confidence: 59%
“…While the Trophic AAs are not used for baseline reconstruction, they are key for the reconstruction of paleo‐food web structures . Given the identical hydrolysis conditions, and the close match of the Source AA group values, it seems unlikely that these offsets are linked to sample preparation, a conclusion supported by recent CSI‐AA method tests with decalcification and hydrolysis of tooth material . Furthermore, recent data from deep‐sea corals has also documented similar offsets between soft tissue and structural protein skeleton, again only in the Trophic AA group (McMahon, personal communication).…”
Section: Discussionmentioning
confidence: 96%
“…, Brault et al . ), therefore the decalcification process was assumed to have negligible effect on isotope ratios.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is a decrease in the mean δ 13 C values after the first acidification technique and a small increase after the second one. The inorganic carbon is more enriched in 13 C than the organic carbon, so decreases in δ 13 C values indicate that the inorganic carbon was removed from the tissue. A decrease in C:N ratios can be evidence of the elimination of inorganic carbon as well, as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%